(untitled) - Gina Tarditi (Gaceta Mexicana de Oncología)
Background: Patients autonomy (PA) and advance care planning (ACP) are cardinal features within the doctor–patient relationship. Nonetheless, little is known in Mexico about oncologists’ perspectives on these issues. Objectives: To explore the roles and responsibilities medical oncologists working in Mexico City perceive themselves as having when discussing and implementing ACP, supporting PA, and the challenges they encounter on these issues in their practice. Methods: Qualitative, semi-structured, in-depth interviews with 10 oncologists working in Mexico City. A thematic analysis approach was used for interpreting interviews. Results: Paternalism has an influence in and beyond the medical field in Mexico, and so it may be better understood as a cultural script. Further, ACP is mainly understood as end-of-life care planning, and the concept of relational autonomy is almost unknown. Health system fragmentation and a lack of communication skills are identified as additional obstacles. Conclusion: To narrow the gap between theory and practice, it is important to develop a consensus over ACP's definition, aims, and scope. Finally, it is important to understand better how Mexican paternalism, as a cultural script, reinforces the paternalistic model of care, which limits PA.